Innovative Surveillance of Dengue, Chikungunya, and Zika Viruses in Aedes aegypti and Aedes albopictus - โกยดุลย์ สุรชาติ (Journal of Health Science of Thailand, 2022)
The purposes of this research were to (1) assess the accuracy of RT-PCR technique to detect dengue (DENV), chikungunya (CHIKV), and zika (ZIKV) viruses in Aedes vectors and (2) analyze the sources of transmission of DENV, CHIKV and ZIKV viruses. Six representative study sites of collecting Aedes pools and surveying households with their ecology between August and September 2017 included village No. 2 and No. 6, Boput subdistrict, Samui district, Suratthani province, Getho community and Takdad community, Kathu subdistrict, Kathu district, Phuket province, and village No 2 and No. 9, Kalai subdistrict, Takuathung district, Phangnga province. Approximately 200 houses of each study site (totally 619) were surveyed using survey form and geo-referenced using GPS device and 100 Aedes pools (totally 300) were collected using the handheld aspirators. All Aedes pool samples were used for preparing the RNA extracts as templates subjected to the RNA amplification of DENV, CHIKV, and ZIKV by RT-PCR, as compared to positive and negative controls. Research findings demonstrated the coinfection of DENV (DENV 1, DENV 2, and DENV 3) and CHIKV found in one pool (1.0%) of Ae. aegypti obtained from Suratthani, and the DENV 1 infection in one pool (1.0%) of Ae. aegypti obtained from Phuket. As for Phangnga, none was positive for any virus. The RT-PCR was highly sensitive and specific for the detection of DENV, CHIKV, and ZIKV present in Aedes pools. This technique can be used as direct epidemiological assessment tool for identifying the hotspot of DENV and CHIKV in Ae. aegypti that circulated within 100-m radius of an Aedes-infected house in Boput subdistrict, Samui district, Suratthani. Similarly, it assessed the hotspot of DENV in Ae. aegypti that circulated within 100-m radius of an Aedes-infected house in Kathu subdistrict, Kathu district, Phuket, based on the information on geographics, epidemiology, entomology, and house survey. This innovative entomo-virological surveillance could identify early circulation of DENV, CHIKV และ ZIKV and provide a trigger for timely and focalized vector control actions.